2016
DOI: 10.1175/waf-d-15-0166.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Calibrated Week-2 Probabilistic Forecast Skill to Reforecast Sampling of the NCEP Global Ensemble Forecast System

Abstract: The final published version of this manuscript will replace the preliminary version at the above DOI once it is available.If you would like to cite this EOR in a separate work, please use the following full citation:Ou, M., M. Charles, and D. Collins, 2016: Sensitivity of calibrated week-2 probabilistic forecast skill to reforecast sampling of the NCEP Global Ensemble Forecast System. Wea. Forecasting. Abstract 21 22CPC requires the reforecast-calibrated GEFS to support the production of their 23 official 6-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The calibration of the ensemble forecast system is evaluated via the RMSE (Zhu and Toth 2008) and rank probability skill score (RPSS; Wilks 2011). The RPSS is frequently used for evaluating the performance of probabilistic forecasts (Ou et al 2016;Melhauser et al 2016;Zhu et al 2017), which measures the improvement of a multicategory forecast relative to a reference analysis. The higher the RPSS, the more skillfully the probabilistic system performs.…”
Section: Bias Correction For Weeks and 4 A Methodology And Analysis Adjustmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The calibration of the ensemble forecast system is evaluated via the RMSE (Zhu and Toth 2008) and rank probability skill score (RPSS; Wilks 2011). The RPSS is frequently used for evaluating the performance of probabilistic forecasts (Ou et al 2016;Melhauser et al 2016;Zhu et al 2017), which measures the improvement of a multicategory forecast relative to a reference analysis. The higher the RPSS, the more skillfully the probabilistic system performs.…”
Section: Bias Correction For Weeks and 4 A Methodology And Analysis Adjustmentmentioning
confidence: 99%
“…The sensitivity of forecast skill to the number of training years has been studied by Hamill et al (2004), Guan et al (2015), and Ou et al (2016). Using the firstgeneration GEFS reforecast dataset, Hamill et al (2004) demonstrated that there was a significant increase in skill from 2 to 5 years of training data for week 2 surface temperature, but only showed small incremental increases by 10-12 years.…”
Section: Skill Sensitivity To Number Of Training Yearsmentioning
confidence: 99%
See 3 more Smart Citations